Travel and tourism : optional units, advanced GNVQ - Youell, Ray. (Longman, 1996)
Travel agency operations. Leisure travel services. Worldwide travel destinations. Tour operations. Tourist attractions. Tourism development. Promotional techniques in travel and tourism.